2006
DOI: 10.1142/s0218301306004715
|View full text |Cite
|
Sign up to set email alerts
|

FORM FACTORS OF ργ*→π0and γγ*→π0TRANSITIONS FROM THE FINITE-WIDTH LIGHT-CONE LOCAL QCD SUM RULES

Abstract: Instead of the usual zero-width approximation, the finite-width approximation for the resonance, the ρ-ω mesons, is used to investigate the light-cone local QCD sum rules for the form factors of the transitions, ργ*→π0and γγ*→π0. To be more certain, a product of two weight functions is chosen in the method of the analytic continuation by duality to annihilate the uncertainty in the continuum region and the integrand in the integration range not covered by vector-meson dominance and where the theoretical expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Comparing the theoretical results with the experimental data, useful constraints on the shape of the pion DA in terms of confidential regions for the Gegenbauer coefficients a 2 and a 4 can be obtained. Recently a quite different sum rule, namely the light-cone sum rule based on the analytic continuation by duality (ACD) [5,24,25], has been used to analyze the γ γ * → π 0 transition form factor. It is found that the ACD sum rule provides a reliable way to extract the form factor F γ π from F γ * π (Q 2 , q 2 ), and the rescaled form factor is consistent with the experimental results at least for Q 2 less than 10 GeV 2 [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the theoretical results with the experimental data, useful constraints on the shape of the pion DA in terms of confidential regions for the Gegenbauer coefficients a 2 and a 4 can be obtained. Recently a quite different sum rule, namely the light-cone sum rule based on the analytic continuation by duality (ACD) [5,24,25], has been used to analyze the γ γ * → π 0 transition form factor. It is found that the ACD sum rule provides a reliable way to extract the form factor F γ π from F γ * π (Q 2 , q 2 ), and the rescaled form factor is consistent with the experimental results at least for Q 2 less than 10 GeV 2 [24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently a quite different sum rule, namely the light-cone sum rule based on the analytic continuation by duality (ACD) [5,24,25], has been used to analyze the γ γ * → π 0 transition form factor. It is found that the ACD sum rule provides a reliable way to extract the form factor F γ π from F γ * π (Q 2 , q 2 ), and the rescaled form factor is consistent with the experimental results at least for Q 2 less than 10 GeV 2 [24]. However, for the special case when both photons are on the mass shell, no satisfactory results of F γ π (0) could be expected by simply extrapolating…”
Section: Introductionmentioning
confidence: 99%